Legal Drugs Are Good Drugs And Illegal Drugs Are Bad Drugs - Indrati, Dina; Prasetyo, Herry (Nurse Media Journal of Nursing, 2011)
Background: Labelling drugs are important issue nowadays in a modern society. Although it is generally believed that legal drugs are good drugs and illegal drugs are bad drugs, it is evident that some people do not aware about the side effects of drugs used.Objective: Therefore, a key contention of this philosophical essay is that explores harms minimisation policy, whether legal drugs are good drugs and illegal drugs are bad drugs and explores relation of drugs misuse in a psychiatric nursing setting and dual diagnosis.Discussion: The drugs misuse will be poor circumstance when it is used by people who suffer from mental illness.Conclusion: The usage of those drugs may be strongly under controlled and medical reasons. Key words: Legal, good drugs, illegal, bad drugs.